Touch the reality : rethinking keywords of political performance - Krejs, Christiane; Probst, Ursula Maria; Ventura, Holger Kube; Mosquera, Gerardo (Wien : Verlag für moderne Kunst, 2016)
al Halabi, Akram ; Bolt, Catrin ; Bruguera, Tania ; Čmajčanin, Lana ; Conceição, Giorgia ; Costa, Pêtra ; Cruz, Sofia ; Dabelka, Masha ; EsRAP ; Fadhel, Kadir ; García, Fidel ; Hiersleitner, Markus ; [et al.]
Touch the reality - rethinking keywords of political performance, Kunstraum Niederoesterreich, Wien, October 21 to December 3 2016
boek